Potential of Hevea brasiliensis Clones, Eucalyptus pellita and Eucalyptus tereticornis Wood as Raw Materials for Bioenergy Based on Higher Heating Value - Menucelli, Joao Roberto; Amorim, Erick Phelipe; Menezes Freitas, Miguel Luiz; Zanata, Marcelo; Cambuim, Jose [UNESP]; Teixeira de Moraes, Mario Luiz [UNESP]; Yamaji, Fabio Minoru; Silva Junior, Francides Gomes da; Longui, Eduardo Luiz (Springer, 2019)
About 11% of the world's primary energy consumption comes from biomass. However, a continuing material deficit indicates the need to find suitable timber for use as bioenergy. In this context, this study aims to determine some chemical and energetic properties, wood density, and fiber features of 10 Hevea brasiliensis clones, including Eucalyptus tereticornis and E. pellita species, to understand how the characteristics of studied woods might interfere with higher heating value (HHV) and determine if these woods and their residues would present potential for bioenergy. In general, HHV results corroborate those in the literature, e.g., E. pellita (16,502 kJ kg(-1)) lower value, and MT45 H. brasiliensis clone (19,757 kJ kg(-1)) higher value, and woods with higher extractive contents and lignin content, but lower holocellulose content, of wood pulp, in addition to denser woods with longer fibers and thicker walls, are woods considered to have higher heating values and, hence, indicated as potential woods for use in bioenergy. However, it is suggested that wood characteristics should be analyzed together to determine the most suitable material for use in bioenergy since a high value of one factor influencing HHV would not, in and of itself, establish suitability of the wood for bioenergy. Nonetheless, all wood samples could have their waste exploited for bioenergy since they range from 16,502 kJ kg(-1) in E. pellita to 19,757 kJ kg(-1) in the MT45 clone of H. brasiliensis.
Keywords: Extractives; Holocellulose; Lignin; Wood density; Wood fibers